2018
DOI: 10.1111/jpc.14168
|View full text |Cite
|
Sign up to set email alerts
|

Specific learning disability

Abstract: Specific learning disabilities (SLD) have an impact on discrete areas of academic function. They result in a level of difficulty that is unexpected when considered in the context of a student's overall intellectual and academic competence. A common example is dyslexia, an SLD that affects the acquisition of literacy. Medical professionals have an important role to play in the evaluation and management of SLD. The medical role is founded on the fact that these conditions are biologically based and have the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Since 1980 a lot of studies have shown interest in the primary "signs" or indications of learning difficulties from the early years (McDonald, 2018). More specifically, it has become generally accepted, through the years, that two are the main areas of early development in which signs of subsequent learning difficulties can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1980 a lot of studies have shown interest in the primary "signs" or indications of learning difficulties from the early years (McDonald, 2018). More specifically, it has become generally accepted, through the years, that two are the main areas of early development in which signs of subsequent learning difficulties can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Öğrenme güçlüğünün nedensel etkenleri incelendiğinde, anksiyete, depresyon, sosyal ve ekonomik yoksunlukların önemi sıkça vurgulanmakla birlikte, genetik aktarımların daha etkili olduğu şeklinde genel bir yaklaşımın hâkim olduğu görülmektedir (Salman ve ark. 2016, McDowell 2018. Öğrenme güçlüğü yaşayan çocuklar sayı, renk, ses, mekân ve zaman gibi kavramların öğrenilmesinde ve ayırt edilmesinde sıklıkla zorluk çekmektedirler (Volden 2013, Deniz ve ark.…”
Section: öğRenme Güçlüğü Ve Oyun Terapisiunclassified
“…One of the part of students who need special educational services is students with specific learning disabilities (SLD). As we know that student with SLD have deficits in the basic psychological processes in SLD with sub-type of dysgraphia, dyslexia and dyscalculia (M. McDowell., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…McDowell., 2018). It will interfere with learning and academic function and these deficits can also lead to emotional and/or behavior problems (Benson, N., & Newman, I, 2010;Backenson., EM Holland., SC, Kubas., HA, Fitzer., KR, Wilcox., G, Carmichael., JA, Fraccaro., RL, Smith., AD, Macoun., SJ, Harrison., GL, Hale., JB, 2015;McDowell., M, 2018). Therefore, it is necessary to identify in advance whether these children can be classified as SLD or not then the right intervention would be provided to achieve the learning targets expected by the school (Fuchs., D, 2012;Reeder., S, 2014;Soares., N, T.…”
Section: Introductionmentioning
confidence: 99%